Penggunaan Aplikasi SIAPIK Bagi UMKM di Balikpapan - Nainggolan, Hermin; Saputra, Dasriyan; Gunawan, Agung; Susilo, Erwin; Handayani, Lilik (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
When it comes to accounting software, MSMEs believe that recording financial statements is difficult, complicated, and superfluous. Bank Indonesia is making an effort to address the problem of capturing and preserving financial information by creating the Micro, Small, and Medium Enterprises (MSMEs) Application. SIAPIK, a mobile and web-based information system for collecting and managing financial data, is a problem that MSMEs commonly face. This service seeks to improve financial literacy by integrating the SIAPIK Application into MSMEs' company operations and using it to generate financial reports that adhere to their Financial Accounting Standards (SAK). Training activities are conducted using the Dialogical Method, the Practice and Assistance Method, and the Lecture Method. According to the results, MSME actors can become more adept with the SIAPIK application, use it for business objectives, and prepare financial reports that meet MSME SAK criteria, which can subsequently be taken into account when asking loans.